The ionic salts with super oxidizing ions O2+ and N5+: Potential candidates for high-energy oxidants - Yang, Xinbo; Li, Nan; Li, Yuchuan; Pang, Siping (Frontiers in Chemistry, 2022)
As an important component of energetic materials, high-energy oxidant is one of the key materials to improve their energy. The oxidizability of oxidant directly determines the intensity of combustion or explosion reaction. It is generally believed that when the nature of reductant is certain, the stronger the oxidizability, the more intense the reaction. Dioxygenyl cation (O2+) and pentazenium cation (N5+) are two kinds of super oxidizing ions, which oxidizability are comparable to that of fluorine. A series of high energetic ionic salts with O2+, N5+ and various anions as active components are designed, and the results show that: 1) Most ionic salts have appropriate thermodynamic stability, high density (up to 2.201 g/cm3), high enthalpy of formation (up to 1863.234 kJ/mol) and excellent detonation properties (up to 10.83 km/s, 45.9 GPa); 2) The detonation velocity value of O2 (nitrotetrazole-N-oxides) and O2B(N3)4 exceed 10.0 km/s, and the detonation pressure exceed 45.0 GPa because of the O2+ salts have higher crystal density (g/cm3) and oxygen balance than that of N5+salts; 3) With a higher nitrogen content than O2+, the N5+ salts have higher enthalpy of formation, which exceed 330 kJ/mol than that of O2+ salts; 4) The linear spatial structure of N5+ leads the salts to reduce their density. Encouragingly, this study proves that these super oxidizing ions have the potential to become high-energy oxidants, which could be a theoretical reference for the design of new high energetic materials.